Experimental analysis and CFD simulation of infrared apricot dryer with heat recovery. Issue 6 (26th April 2017) - Aktaş, Mustafa; Sözen, Adnan; Amini, Ali; Khanlari, Ataollah
ABSTRACT: Drying is one of the easily accessible and the most widespread processing technologies that have been used since ancient times for preserving fruits. Drying is an energy-intensive and time-consuming process, so reducing energy demand is important. The main aim of this paper is to analyze the heat and mass transfer characteristics of product in the drying chamber and in addition to this, three-dimensional (3-D) computational fluid dynamic (CFD) simulation was performed. The analyses of heat and mass transfer were investigated theoretically and experimentally in infrared dryer (IRD). The dryer consists of air to air heat recovery unit and proportional temperature controller. Experiments were performed at 0.5 and 0.25 m/s air velocities and at 60 and 65°C apricot surface temperatures which were controlled by three thermocouples contacted on top side of the product. In order to use energy more effectively and improve the drying characteristics of apricot, analyses were performed under different drying conditions. Since the heat recovery unit has a key role in this system, the performance of this unit was investigated and recovered energy ratio was between 58 and 62%. The calculated moisture diffusivity values varied from 1.7 × 10 −10 to 1.15 × 10 −9 for apricot, and the highest value of average energy efficiency was obtained as 16.43% at 65°C temperature and 0.25 m/s air velocity. Theoretical and experimental results are in line with each other.